Splash Basins in the Operating Room: Clean or Contaminated? A Study on Bacterial Contamination in Splash Basins Used to Rinse Surgical Instruments During Surgery - Karoline Stavang Michalsen; Linda Helen Helgeland; Grethe Myklestul Dåvøy; Marit Hegg Reime; Fred-Ivan Kvam (Nursing Reports)
Background: Preventing postoperative infection and promoting patient safety are essential responsibilities of the operating room nurse. In some hospitals, splash basins are used to rinse instruments during surgery, although previous studies emphasise the risk of bacterial contamination. A recent systematic review calls for further investigation into surgical teams’ use of splash basins. Objectives: Our objective was to investigate bacterial contamination in splash basins and to identify the variables that may have an influence on this contamination. Methods: This prospective observational pilot study involved collecting, cultivating, and analysing water samples obtained from splash basins during operations performed in the thoracic and neurosurgical departments. The ventilation systems, length of surgery, number of instruments in the splash basin, number of persons present in the operating room, frequency of door openings during surgery, and type of bacteria were observed. Results: Bacterial growth was found in 44% of the final water samples: 41% from the thoracic surgical department, which had laminar airflow ventilation systems/unidirectional airflow ventilation, and 47% from the neurosurgical department, which had conventional ventilation systems/turbulent mixing ventilation. However, the binary logistic regression analysis revealed no significant correlation between bacterial growth and the ventilation systems, length of surgery, number of instruments in the splash basin, number of people in the operating room, or frequency of door openings. The most common types of bacteria found were coagulase-negative staphylococci and Micrococcus luteus. Conclusions: Splash basins become contaminated with bacteria during surgery. Therefore, using splash basins with sterile water is not recommended. Further research is needed to determine the best evidence-based practice for rinsing instruments perioperatively.